169k views
3 votes
(6x2 + 4x2 - 6x - 4) = (2x - 2)

User Iamafasha
by
5.0k points

1 Answer

5 votes

Answer:

x = -1/5, x = 1

Explanation:

Maybe you want to find x.

Subtract the right side and collect terms.

6x^2 +4x^2 -6x -4 -(2x -2) = 0

10x^2 -8x -2 = 0

5x^2 -4x -1 = 0 . . . . . . divide by 2

(5x +1)(x -1) = 0 . . . . . . factor

Solutions are the values of x that make these factors zero:

5x +1 = 0 ⇒ x = -1/5

x -1 = 0 ⇒ x = 1

Solutions are x = -1/5, x = 1.

User Mrhn
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.